2011
DOI: 10.1186/1476-511x-10-46
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin synthase overexpression increases cholesterol accumulation and decreases cholesterol secretion in liver cells

Abstract: BackgroundStudies have shown that plasma high density lipoprotein cholesterol levels are negatively correlated with the development of atherosclerosis, whereas epidemiological studies have also shown that plasma sphingomyelin level is an independent risk factor for atherosclerosis.MethodsTo evaluate the relationship between cellular sphingomyelin level and cholesterol metabolism, we created two cell lines that overexpressed sphingomyelin synthase 1 or 2 (SMS1 or SMS2), using the Tet-off expression system.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
(38 reference statements)
1
26
0
Order By: Relevance
“…[1][2][3][4] Previously, we studied the structure of the human SGMS1 gene and characterized transcripts of this gene that are potentially able to direct protein synthesis. We established that the transcriptional diversity of the SGMS1 gene is provided by the presence of alternative promoters, alternative polyadenylation and exon splicing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Previously, we studied the structure of the human SGMS1 gene and characterized transcripts of this gene that are potentially able to direct protein synthesis. We established that the transcriptional diversity of the SGMS1 gene is provided by the presence of alternative promoters, alternative polyadenylation and exon splicing.…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus-mediated SMS1 and SMS2 overexpressions lead to increased liver SMS activity, which contributes to the increased plasma SM levels [10]. SMS overexpression-mediated SM increases paralleled the cholesterol content changes in a human hepatoma cell line [47]. Conversely, SMS2-deficient mice showed a significant decrease in plasma SM levels either on a chow diet or on a high-fat diet [26].…”
Section: Discussionmentioning
confidence: 96%
“…Increased sphingomyelin content impaired (LCAT)-mediated maturation and is attributed to HDL deficiency. Further, recent studies have found that augmented expression of SMS increased the levels of intracellular SM, cholesterol, and apolipoprotein A-I within Huh7 cells [47]. Overexpressions of both SMS1 and SMS2 increased cellular SM and DAG levels and induced TNF-α-mediated CHO cell apoptosis [9].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, patients with Niemann-Pick disease cannot hydrolyze SM due to defective SMase, resulting in the accumulation of SM and cholesterol in the liver and the nervous system (33). Additionally, because ABCA1 is a transmembrane protein that is located in or near the lipid raft, some researchers have implied that the enhancement of SM and cholesterol may also increase the ABCA1 expression in cells (32).…”
Section: Discussionmentioning
confidence: 99%